Integration of Discourse Analysis in Life Scope Learning: Generation Z's Ecological Literacy Construction of Climate Representation in Modern Media - M.Ichsan Ali; Suarlin Suarlin; Asri Ismail; Deni Indrawan (Journal of Innovative and Creativity, 2025)
The study aims to analyze the representation of climate crisis discourse in modern media using Fairclough’s Critical Discourse Analysis (CDA) framework. It focuses on how language is used to frame climate change issues, uncover underlying ideologies, and examine power relations among state actors, corporations, and civil society. Employing a qualitative approach with a case study design, the research analyzes news texts discussing climate change, energy transition, and environmental policies. Data were examined through the three CDA dimensions, textual, discursive, and social practices, to reveal meaning construction and ideological tendencies within media narratives. The findings indicate that climate crisis discourse in the media predominantly emphasizes technocratic solutions, institutional moral responsibility, and international cooperation, while marginalizing civil society participation. At the social level, media reproduce the ideology of green capitalism and sustainable development that prioritize efficiency, investment, and global partnership. The results demonstrate that climate issue representation in media is not neutral but shaped by economic–political interests and global power structures. Therefore, fostering critical media literacy and promoting inclusive, transformative alternative discourses are essential for developing ecological awareness among younger generations, particularly Generation Z.